2008
DOI: 10.1002/jcp.21539
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of macrophage TNFα production by orthopaedic wear particles requires activation of the ERK1/2/Egr‐1 and NF‐κB pathways but is independent of p38 and JNK

Abstract: Bone loss that causes aseptic loosening of orthopaedic implants is initiated by pro-inflammatory cytokines produced by macrophages in response to implant-derived wear particles. MAPK and NF-κB signaling pathways are activated by the particles; however, it is not clear which of the signaling pathways are important for the initial response to the wear particles and which are only involved at later steps in the process, such as osteoclast differentiation. Here, we show that the ERK1/2, p38, JNK, and NF-κB pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 91 publications
0
19
0
1
Order By: Relevance
“…Whether hyperoxia and cav-1 have any interactions with these pathways to regulate survivin requires further investigation. In addition, previous studies have shown that the mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK), p38 MAPK, and PI3-kinase pathways contributed to the activation of Egr-1 in response to hyperoxia (4,7,38,49). These pathways are likely to regulate cav-1-mediated apoptosis and downregulation of survivin, given that ERK/PI3-kinase are altered in cav-1 Ϫ/Ϫ (12).…”
Section: Discussionmentioning
confidence: 99%
“…Whether hyperoxia and cav-1 have any interactions with these pathways to regulate survivin requires further investigation. In addition, previous studies have shown that the mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK), p38 MAPK, and PI3-kinase pathways contributed to the activation of Egr-1 in response to hyperoxia (4,7,38,49). These pathways are likely to regulate cav-1-mediated apoptosis and downregulation of survivin, given that ERK/PI3-kinase are altered in cav-1 Ϫ/Ϫ (12).…”
Section: Discussionmentioning
confidence: 99%
“…In many conditions Egr-1 is a downstream target of phosphorylated MAPKs, which means that the activation of Egr-1 is dependent on MAPKs phosphorylation [20,21]. In this report we explored whether silica could induce the activation of Egr-1 in A549 cells and mediated by MAPKs.…”
Section: Introductionmentioning
confidence: 99%
“…25 It has been shown that adherent endotoxin substantially enhances the effects of wear particles on pro-inflammatory cytokine production, osteoclast differentiation and osteolysis through stimulation of MAPK and NF-κB activation induced by wear particles. 26 After release, wear particles may be coated by different molecules (e.g. lipids, carbohydrates, proteins) and this coating may then evoke a reaction of the innate or acquired immune system.…”
Section: 3mentioning
confidence: 99%